CRISPReader System Sensing the Ets-1 Transcription Factor Can Effectively Identify Cancer Cells - Yang, Kang; Zhou, Yan; Zhong, Hongcai (Frontiers in Molecular Biosciences, 2021)
By targeting key genes, the CRISPR system can effectively exert its anti-cancer activity. The latest research suggests that the CRISPReader system that regulates gene transcription can effectively target and inhibit bladder cancer cells by sensing transcription factors such as c-Myc and Get-1 in the cell. An interesting question is whether the CRISPReader system can exert its anti-cancer ability against a variety of tumors by sensing the broad-spectrum transcription factor Ets-1. In this work, a CRISPReader system that senses the Ets-1 transcription factor has been constructed. It can effectively identify a variety of cancer cell lines, and specifically induce apoptosis in cancer cells. This study fully confirmed the effectiveness of Ets-1 as a broad-spectrum cancer related signal and provided a new anti-cancer tool based on the CRISPReader system.